Ways of thinking about ethics - Parker, M; Hope, T (2004)
The practice of medicine involves not only scientific and technical knowledge, but also value judgements. Such judgements should be properly analysed and assessed, just as scientific evidence should be properly evaluated. Assessment of value judgements may require several different approaches, including reasoning from fundamental moral theory or from general principles, clarification of key concepts, and comparison with specific cases to ensure consistency. Focusing on the logical structure of argument can help ensure that rhetorical devices are not used to make an invalid argument persuasive. Doctors must be prepared to justify their decisions and actions with regard to both the evidential scientific basis, and the ethical values and process of decision-making. It is sometimes helpful, when faced with an issue in medical ethics, to step back and consider fundamental approaches to ethics. Two contrasting approaches have been particularly influential in western ethics in general, and in medical ethics in particular: consequentialist ethics (notably utilitarianism) and duty-based ethics. © 2004 Elsevier Ltd. All rights reserved.